Language Mastery of Refugee Children in Malaysia Despite Adverse Circumstances - Fernandez Aspin, Janet; Cheong, Loh Sau (Universitas Mercu Buana, 2019)
Â Refugee education is a challenge to the Malaysian government, with the ever rising influx of refugees into the country. Malaysia has policies in place whereby refugee children are not entitled or allowed an education in the government school system. They are encouraged to secure private education. The researcher was appointed as the external examiner for Year Six, the final year of Primary Education, whereby it was noted that a number of students had mastery of languages despite their adverse circumstances as refugee children.Â Eleven students from the refugee camp were randomly selected on the basis of anonymity. They were interviewed within a secure environment and this data was analysed along with the test answer scripts. The study seeks to explore plausible reasons for their language mastery despite adverse circumstances and offers insights for the findings to be applied within a local context where English is taught as a second language.Â Key words: refugee, education, mastery, languages